Novel induced charge electrokinetic based microfluidic design for trapping of micro and nanoparticles: Numerical simulation approach. (26th October 2021) - Salimian Rizi, Farideh; Talebi, Shahram; Mohammadi, Mehdi
Abstract: ICEK phenomena have recently been used for separating particles. The most critical issue in separating the nanoparticles (e.g., exosome, viruses, or bacteria) in complex biofluids is implementing a two‐step procedure (I) trapping the larger particles (e.g., red blood cells) from the blood and (II) trapping the nanoparticles. The purpose of this paper is to propose a design framework for the separation of considered particles in one chip. The model considered evaluating the feasibility of two‐step micro and nanoparticle separations, for instance, exosome (30–120 nm) from red blood cells (5–7 μm) or other cells in biological samples. A low voltage direct current (DC) electric field is used to generate vortices around the obstacles to trap microparticles (e.g., red blood cells) and nanoparticles (e.g., exosome) before the first and second obstacles, respectively. The achieved results demonstrated that the generated vortices are adequately strong to trap both micro and nanoparticles. This chip has several advantages, consisting of low voltage requirement and easy to manufacture design.